Covid-19 a brief Overview - Sania Tariq; Muhammad Hamza; Ayesha Muazzam; Areeb Ahmer; M.Talha Mumtaz; Shehroz Ahmad (Brilliance: Research of Artificial Intelligence, 2022)
In December 2019, pneumonia brought on by the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection first appeared in Wuhan City, Hubei Province, China. The World Health Organization (WHO) will formally refer to the illness brought on by SARS-CoV-2 infection as coronavirus disease by February 11, 2020. (COVID-19). Fever, a dry cough, and exhaustion are the most common clinical symptoms of COVID-19, and pulmonary involvement is often evident. Being extremely infectious, SARS-CoV-2 may infect the majority of people in the general population. Currently, the major sources of the illness, which is spread by respiratory droplets and direct contact, are infected individuals and wild animal hosts. Since the outbreak, the Chinese government and scientific community have moved quickly to uncover the underlying cause, disclose the viral DNA sequence, and implement control measures. While past studies have concentrated on epidemiology, clinical characteristics, diagnosis, treatment, as well as the development of drugs and vaccines, current research has uncovered crucial parts of SARS-CoV-2 biology and disease pathogenesis. This review tries to establish agreement among experts by summarising the most recent study results. Along with current advice for prevention, containment, and essential treatment of this pandemic, we will also discuss existing initiatives and experience from China that may provide light on how to curb the outbreak and further our knowledge of this newly emergent infectious illness.